Strategi Kepemimpinan di Lurah Ganting Parak Gadang - Santia, Indah; Syamsir , Syamsir; Sepvani, Nadira; Ayu, Niken (Inovan Publisher, 2024)
Leadership (leadership) which means the ability and personality of a person to influence people or other parties so that these parties carry out activities in accordance with the rules to achieve goals that have been set together. Which in this study looks at how the leadership style in the Ganting Parak Gadang village head, the factors that influence it and how the leadership strategy is set in the Ganting Parak Gadang village head. Leaders who direct others to achieve optimal employee performance in Lurah ganting Parak Gadang. The method used in this research uses qualitative methods The data obtained in the field will be analyzed descriptively qualitative. Qualitative analysis is used to describe how the leadership style in the Ganting Parak Gadang lurah office. The leadership style of the Head of Ganting Parak Gadang is a Democratic leadership style. Which is where the Head of Ganting Parak Gadang always provides his community by communicating directly with his citizens in the field. Lurah Ganting Parak Gadang also always opens communication with the community, namely by providing opportunities for each community to express ideas or ideas in it. As for some factors that influence the Head of Village in improving leadership, namely high work discipline employees do not just appear but are a continuous learning process. This leadership must have a role or authority in leading a company or a job where in this leadership we must build cooperation, the ability to influence with good things, and provide useful benefits to staff or employees.